Brilliant bites : 75 amazing small bites for any occasion - Brown, Maegan (Rock Point, 2023)
"Bestselling cookbook author Maegan Brown (a.k.a. The BakerMama) continues her quest to share her best ideas for effortless entertaining with 75 charming small bites that are easy to make and amazing to eat!"-from back cover.